2016
DOI: 10.1177/2333794x16635464
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Interval Aminoglycoside Use in Cystic Fibrosis Exacerbation in Children and Young Adults

Abstract: This is a prospective quality improvement project for patients with cystic fibrosis who are 5 years of age and older who were admitted for intravenous antibiotic administration as part of treatment of cystic fibrosis exacerbation. The goal of this project was to compare the pharmacokinetics of once-daily versus thrice-daily aminoglycoside use when treating cystic fibrosis exacerbation in different age groups. Of the total of 119 patient encounters, 82.4% were started on once-daily dosing, and the remainder wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the pediatric and adult literature, concerns with extended interval dosing have also been raised about possible bacterial regrowth during the drug-free interval. 32,33 Although there are several different neonatal empiric gentamicin regimens proposed in the literature, the optimal regimen has not been identified. Efficacy of gentamicin has most commonly been associated with a peak to MIC ratio of 8 to 10:1.…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric and adult literature, concerns with extended interval dosing have also been raised about possible bacterial regrowth during the drug-free interval. 32,33 Although there are several different neonatal empiric gentamicin regimens proposed in the literature, the optimal regimen has not been identified. Efficacy of gentamicin has most commonly been associated with a peak to MIC ratio of 8 to 10:1.…”
Section: Discussionmentioning
confidence: 99%
“…While the study demonstrated that aminoglycoside clearance was higher in younger patients, its limitations including study design and small sample size limit its applicability to practice. 29 The TOPIC study was the largest study area. 34 The NINJA program was implemented at multiple centers to reduce AKI in hospitalized children related to nephrotoxic medication exposure.…”
Section: Dosing Strategiesmentioning
confidence: 99%
“…However, there was no discussion on how the change impacted efficacy via FEV 1 or the incidence of nephrotoxicity. While the study demonstrated that aminoglycoside clearance was higher in younger patients, its limitations including study design and small sample size limit its applicability to practice 29 . The TOPIC study was the largest study conducted in both adult and pediatric patients with CF in which PK data was collected systematically.…”
Section: Dosing Strategiesmentioning
confidence: 99%